Studies on Schismatoglottideae (Araceae) of Borneo XXXXV: The flowering and fruit development of Schismatoglottis tecturata - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2014)
The flowering and fruit development of Schismatoglottis tecturata (Schott) Engl.is illustrated.